Inhibition of Dengue Virus by Targeting Viral NS4B Protein - Xie, Xuping (American Society for Microbiology, 2011)

(untitled)
We report a novel inhibitor that selectively suppresses dengue virus (DENV) by targeting viral NS4B protein. The inhibitor was identified by screening a 1.8-million-compound library using a luciferase replicon of DENV serotype 2 (DENV-2). The compound specifically inhibits all four serotypes of DENV (50% effective concentration [EC(50)], 1 to 4 μM; and 50% cytotoxic concentration [CC(50)], >40 μM), but it does not inhibit closely related flaviviruses (West Nile virus and yellow fever virus) or nonflaviviruses (Western equine encephalomyelitis virus, Chikungunya virus, and vesicular stomatitis virus). A mode-of-action study suggested that the compound inhibits viral RNA synthesis. Replicons resistant to the inhibitor were selected in cell culture. Sequencing of the resistant replicons revealed two mutations (P104L and A119T) in the viral NS4B protein. Genetic analysis, using DENV-2 replicon and recombinant viruses, demonstrated that each of the two NS4B mutations alone confers partial resistance and double mutations confer additive resistance to the inhibitor in mammalian cells. In addition, we found that a replication defect caused by a lethal NS4B mutation could be partially rescued through trans complementation. The ability to complement NS4B in trans affected drug sensitivity when a single cell was coinfected with drug-sensitive and drug-resistant viruses. Mechanistically, NS4B was previously shown to interact with the viral NS3 helicase domain; one of the two NS4B mutations recovered in our resistance analysis—P104L—abolished the NS3-NS4B interaction (I. Umareddy, A. Chao, A. Sampath, F. Gu, and S. G. Vasudevan, J. Gen. Virol. 87:2605-2614, 2006). Collectively, the results suggest that the identified inhibitor targets the DENV NS4B protein, leading to a defect in viral RNA synthesis.